2003
DOI: 10.1128/aem.69.9.5336-5342.2003
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of Tetracycline Resistance Genes Isolated from Fish Farm Bacteria to Those from Clinical Isolates

Abstract: Tetracycline-resistant (Tet r ) bacteria were isolated from fishes collected at three different fish farms in the southern part of Japan in August and September 2000. Of the 66 Tet r gram-negative strains, 29 were identified as carrying tetB only. Four carried tetY, and another four carried tetD. Three strains carried tetC, two strains carried tetB and tetY, and one strain carried tetC and tetG. Sequence analyses indicated the identity in Tet r genes between the fish farm bacteria and clinical bacteria: 99.3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
143
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(158 citation statements)
references
References 48 publications
7
143
2
6
Order By: Relevance
“…(PALLERONI;BRADBURY, 1993;OLIVEIRA-GARCIA et al, 2002), can be found in a variety of geographical regions, environments and decomposing organic materials (rivers, wells, reservoir lakes, soil, raw milk, frozen fish, eggs, animal carcasses, hospital equipment and environment, semen, frozen bovine embryos, human anatomical sites and urine) (KONEMMAN et al, 2001;ALMEIDA et al, 2005). It has also been reported in goats and crocodiles (HARRIS; ROGERS, 2001) and in fish like Seriola quinqueradiata (FURUSHITA et al, 2003) and Ictalunes punctatus (DU et al, 2011). Depending on the strain isolated, it may have pathogenic activity against both humans and animals (CHANSANG et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…(PALLERONI;BRADBURY, 1993;OLIVEIRA-GARCIA et al, 2002), can be found in a variety of geographical regions, environments and decomposing organic materials (rivers, wells, reservoir lakes, soil, raw milk, frozen fish, eggs, animal carcasses, hospital equipment and environment, semen, frozen bovine embryos, human anatomical sites and urine) (KONEMMAN et al, 2001;ALMEIDA et al, 2005). It has also been reported in goats and crocodiles (HARRIS; ROGERS, 2001) and in fish like Seriola quinqueradiata (FURUSHITA et al, 2003) and Ictalunes punctatus (DU et al, 2011). Depending on the strain isolated, it may have pathogenic activity against both humans and animals (CHANSANG et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…The purified PCR products were sequenced directly using the sequencing primers 27f (AGA GTT TGA TCC TGG CTC AG) (FURUSHITA et al, 2003); 108r (CAG ATT CCC ACG CGT TAC GC) and 420r (TTA CAA CCC TAA GGC CTT C) (LEYS et al, 2004); Amp2 (AAG GAG GTG ATC CAR CCG CA) (WANG et al, 1996); 16S1203f (GAG GTG GGG ATG ACG TCA AGT CCT C); and 16S1110r (TGC GCT CGT TGC GGG ACT TAA CC) (SOARES-RAMOS et al, 2003).…”
Section: Bacterial Identificationmentioning
confidence: 99%
“…Since many antibiotic resistance genes are encoded by transferable elements including plasmids and transposons, cultured fish may serve as a vehicle for transmission of antibiotic resistance to bacteria that are commensal or pathogenic to humans Rhodes et al, 2000 . In our previous study at three different fish farms A, B, and C located in the southern part of Japan Furushita et al, 2003 , we confirmed the presence of conjugative plasmids conferring the resistance to tetracycline, kanamycin and chloramphenicol in four bacteria of three different genera, isolated from cultured yellowtails collected at fish farm A and C. Each fish farm was separated from each other by over 100 km and no reliable data on antibiotic use were obtained from the fish farmers Furushita et al, 2003 . The tetracycline-resistance gene was identified as tetA D Allard et al, 1993 .…”
mentioning
confidence: 95%
“…The 16S rRNA gene was amplified by PCR using primers 27F (5'-AGAGTTTGATCCTGGCTCAG-3 ') in combination with 1492R (5'-TACGG(C/T)TACCTTGTTACGACTT-3') or a combination of two primers, 27f and Amp2R (5'-ACMC AAGGAGGTGATCCARC-3 ') (Heuer et al, 1997;Furushita et al, 2003) min, 60 °C -1 min and 72 °C -2 min and a final extension step at 72 °C -4 min. PCR products were analyzed by electrophoresis in 2 % agarose gel and purified using the kit Wizard® SV Gel and PCR Clean-Up System (Promega).…”
Section: Molecular Characterizationmentioning
confidence: 99%